Analysis of Administrative Structures and Economic Programs of the Ahmad Shahi’s Era (American Journal of Multidisciplinary Research and Innovation, 2022)
Much has been done in the reign of Ahmad Shah for the comfort and convenience of the people and he is considered the founder and pioneer of good government. He loved his people from the core of his heart as he was a kind-hearted leader and had respect to them, therefore, he was given the title of "Baba" and was given special devotion and was considered as the saint of Allah. The purpose of the research study is deeply analyzing the administrative and economic structure of Ahmad Shah’s government. Besides, to identify those factors which positively affect the economic and administrative structure of Ahmad Shah’s government. As well as, to explain the overall leadership in the era of Ahmad Shah. The doctrinal research methodology and a descriptive, explanatory, and analytical research approaches are used in this work. It is worth mentioning that this research study is entirely based on library sources. Most of the sources are reputable and trustworthy textbooks, scholarly published and unpublished journal articles, law reports, and online websites related to the research area. According to well-known historians and the study of history in terms of administrative and economic structure and achievements the government of Ahmad Shah was considered one of the advanced governments of the era. The researcher suggests and recommend to the central government and to the local governments of Afghanistan as well as to the regional governments that to deeply study the administrative and economic structure, achievements, and reforms of the Ahamad Shah era and try to implement them in their central and local institutions. Furthermore, the researcher has a suggestion for the other researchers to work on the military, political, and social structure of Ahmad Shah’s government in order to squinch the academic thirst of the students, professors, and other people